Interface analysis of ultrathin SiO2 layers between c‐Si substrates and phosphorus‐doped poly‐Si by theoretical surface potential analysis using the injection‐dependent lifetime. (9th November 2020) - Choi, Sungjin; Baek, Jimin; Kim, Taejun; Min, Kwan Hong; Jeong, Myeong Sang; Song, Hee‐eun; Kang, Min Gu; Kim, Donghwan; Kang, Yoonmook; Lee, Hae‐Seok; Myoung, Jae‐Min; Park, Sungeun
Abstract: Passivated contact structures are often representative of tunnel oxide passivated contact (TOPCon) and polycrystalline silicon on oxide (POLO) solar cells. These passivated contact technologies in silicon solar cells have experienced great strides in efficiency. However, characteristics analysis of poly‐Si/SiO2 applied to TOPCon and POLO solar cells as a carrier‐selective and passivated contact is still challenging because the silicon oxide film is very thin (<1.5 nm), poly‐Si and silicon oxide properties change during thermal treatment for passivation effects, and dopant diffusion from poly‐Si layer to the silicon wafer occurs. In this study, the interfacial analysis was performed by applying an algorithm based on the extended Shockley–Read–Hall (SRH) theory to the P‐doped poly‐Si/SiO2 /c‐Si structure. Quantitative parameters of the P‐doped poly‐Si/SiO2 /c‐Si interface were extracted by fitting the measured and simulated lifetime curves with algorithms, such as D it (interface trap density) and Q f (fixed charge), from which we were able to elucidate the passivation effect of the interface. The interface analysis method using this algorithm is meaningful in that it can quantify the passivation characteristics of TOPCon with very thin silicon oxide film. The interface characteristics were also analyzed using the injection‐dependent lifetime after thermal treatment of P‐doped poly‐Si/SiO2 /c‐Si samples for passivation effect. After the 850°C thermal treatment, the following best passivation effects were verified, namely, ψ s = 0.248 eV, D it = 1.0 × 10 11 cm −2 ·eV −1, Q f = 2.4 × 10 12 cm −2, and J 02 = 370 pA·cm −2 . Through the analysis model using carrier lifetime theory, we investigated quantitatively the passivation properties of P‐doped poly‐Si/SiO2 /c‐Si. Abstract : Through the algorithm design and presentation of the lifetime fitting method, it was possible to quantitatively analyze the passivation effects of selective contact. Thin tunnel oxide ( t 1.5 nm) analysis method is presented as the injection‐dependent lifetime analysis method. Through the analysis of solar cells with selective contact structure, it was possible to present the necessary analysis methods for high efficiency.